2020
DOI: 10.1111/jcmm.15113
|View full text |Cite
|
Sign up to set email alerts
|

Down‐regulated lncRNA AGAP2‐AS1 contributes to pre‐eclampsia as a competing endogenous RNA for JDP2 by impairing trophoblastic phenotype

Abstract: Recently, growing evidence has shown that aberrant long non-coding RNA (lncRNA) expression in conjunction with an impaired trophoblastic phenotype could implicate the pathological process of pre-eclampsia (PE). However, only a small portion of lncR-NAs has been characterized with regard to the function and molecular mechanisms involved in PE. There are still gaps in the available knowledge; as a result, there are currently only a few applicable treatments for PE in the context of lncRNA. Here, we found that ln… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Subcellular fractionation was carried out as described by Xu et al 37 Nuclear and cytosolic fractions were prepared from trophoblast cells by using PARIS Kit (Cat. NO.…”
Section: Subcellular Fractionationmentioning
confidence: 99%
“…Subcellular fractionation was carried out as described by Xu et al 37 Nuclear and cytosolic fractions were prepared from trophoblast cells by using PARIS Kit (Cat. NO.…”
Section: Subcellular Fractionationmentioning
confidence: 99%
“…LncRNAs are a group of non-coding RNAs widely distributed in humans ( 23 ), which are different from linear non-coding RNAs such as miRNAs. It has been reported that lncRNAs may mediate upregulation or downregulation of gene expression ( 24 ), and lncRNAs are stable and widely expressed in many tumor tissues ( 25 , 26 ). It suggests the possibility that lncRNAs may be involved in paracrine signaling or cell-to-cell crosstalk.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs are a group of noncoding RNAs widely distributed in humans (19) which are different from linear noncoding RNAs such as miRNAs. It has been reported that lncRNAs may mediate upregulation or downregulation of gene expression and, despite being classified as noncoding, may also encode proteins (20). Moreover, lncRNAs are stable and widely expressed in many tumor tissues (21,22).…”
Section: Discussionmentioning
confidence: 99%